2018
DOI: 10.3390/su10041101
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Cooling Effects of Urban Green Space in Harbin in Terms of Reducing the Heat Island Effect

Abstract: The urban heat island (UHI) effect might cause extreme weather, which would seriously affect people's health, increase energy consumption and cause other negative impacts. To construct urban green spaces is a feasible strategy to effectively weaken the UHI effect. In this study, the cooling effect of green spaces on the UHI effect was carefully investigated in summer and winter in Harbin city. Specifically, the vegetation index and surface temperature information were extracted by the grid method, and based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Many studies of land surface temperature in urban areas have revealed the apparent cooling effects of green spaces and vegetation [67][68][69][70][71], as found in the present study. Taleghani et al's studies in both Los Angeles [60] and Portland [62] show that adding vegetation and increasing the albedo of the pavement can decrease air temperature at 1.5 m. The Los Angeles study [60] shows that green roofs specifically (as opposed to ground-level vegetation) have little cooling effect at 1.5 m height, but mainly provide cooling effects at heights above the pedestrian level (rooftop level).…”
Section: Relationship To Previous Studiessupporting
confidence: 82%
“…Many studies of land surface temperature in urban areas have revealed the apparent cooling effects of green spaces and vegetation [67][68][69][70][71], as found in the present study. Taleghani et al's studies in both Los Angeles [60] and Portland [62] show that adding vegetation and increasing the albedo of the pavement can decrease air temperature at 1.5 m. The Los Angeles study [60] shows that green roofs specifically (as opposed to ground-level vegetation) have little cooling effect at 1.5 m height, but mainly provide cooling effects at heights above the pedestrian level (rooftop level).…”
Section: Relationship To Previous Studiessupporting
confidence: 82%
“…During the city planning process, green areas are considered as the main part of urban development [22]. Most studies related to modern cities have shown that urban green areas play an important role in reducing the LST, particularly inside the city area, by providing cooling [23,24]. Urban green spaces provide cooling to minimize the LST via shading and evaporation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, urban policies can be directed to those areas where the SUHI phenomenon is still present and creates discomfort in the population. Furthermore, the public administration could evaluate appropriate mitigation measures such as green roofs, cool materials, and green areas [64,65] that lead to a more sustainable life quality. In addition, using this methodology, it is possible to evaluate whether the policies entailed within the framework of the European Green Infrastructure Strategies are producing the desired results.…”
Section: Introductionmentioning
confidence: 99%